Tsunami Disaster Risk Assessment Using a Geographic Information System for Puger Sub-District, Jember Regency - Suparno Suparno; Retno Utami Agung Wiyono; Entin Hidayah; Wei Koon Lee (Fakultas Teknik, Universitas Brawijaya, 2023)
The southern region of East Java is located on the Indo-Australian plate. The shifting of these plates allows for earthquakes that trigger tsunamis to occur. The earthquake leads to the impact of a tsunami in several areas, one of which is Puger Sub-District, Jember Regency. The main economic activity of the Puger Sub-District is the fishery; hence significant local coastal communities are vulnerable to tsunami threats. This study aims to map the tsunami risk using a Geographic Information System. The tsunami hazard map used the analysis of the tsunami inundation map from the BMKG. Vulnerability and capacity maps were prepared based on BNPB Chief Regulations. Vulnerability is evaluated based on social, physical, environmental, and economic data. Capacity considers components of the institution, early warning and risk analysis or evaluation, disaster awareness education, reduction of basic risk, and preparedness. The hazard, vulnerability, and capacity maps are classified into five classes. The tsunami risk map is then derived by overlaying the three input maps. Results showed that the villages with very high risk are Puger Kulon and Mojosari at the coastal front areas, covering an area of 13.01% of the total regional area of the Puger Sub-District.